Enhancing the Capacity of Farmers in Peanut Seed Production under the Community Legume Seed Production Center in Khao Suan Kwang Subdistrict, Khon Kaen Province, Thailand - Chaiyachot, Bhornsuda; Choenkwan, Sukanlaya; Chankaew, Sompong (Area Based Development Research Journal, 2025)
The Community Legume Seed Production Center located in Khao Suan Kwang Subdistrict, Khao Suan Kwang District, Khon Kaen Province, Thailand, is a grassroots initiative comprised of local peanut farmers working collectively to produce and distribute high-quality peanut seeds. This Center plays a crucial role in supporting the community’s agricultural productivity, aiming to provide reliable, locally-produced peanut seeds. However, despite the organized effort, the yield of the Khon Kaen 6 peanut variety has remained below the standard benchmarks set by the Department of Agriculture. Recognizing this limitation, twenty active members of the Center collaboratively engaged in a structured capacity-building process with the goal of enhancing both the quality and productivity of peanut seed production.The process adopted a participatory learning and action (PLA) framework, emphasizing knowledge sharing, experiential learning, and practical implementation. The initiative unfolded in five systematic phases: 1) Participatory planning through group meetings: The first step involved organizing group discussions and planning sessions among Center members. These meetings served as platforms for exchanging ideas, identifying key production problems, and co-developing solutions. During this stage, the group recognized several critical issues affecting their seed quality and yield, including low seed purity, inadequate pest management, poor soil conditions, and insufficient post-harvest processing practices. These insights laid the foundation for a collective action plan aimed at improving their practices through collaborative learning. 2) Knowledge acquisition through expert training: The second phase centered on acquiring technical knowledge. The Center invited specialists from the Khon Kaen Seed Research and Development Center to conduct comprehensive training sessions. The workshops covered a range of topics crucial for improving peanut seed production, including land preparation, soil fertility management, pest control, seed selection, and post-harvest handling. Of particular interest was the use of gypsum to improve soil structure and calcium availability, a technique especially beneficial for the Khon Kaen 6 variety. The training also emphasized the importance of using Rhizobium inoculation, dolomite application, and balanced fertilization (16-16-8), which are proven strategies to enhance peanut growth and yield after rice harvests in the region. 3) Experiential learning through field visits: To deepen understanding, the third phase involved experiential learning through field visits. Members traveled to successful peanut farms within the district, observing effective farming techniques implemented by local farmers. These field visits provided practical exposure to pest prevention methods, such as crop rotation and biological control, as well as best practices for soil amendment and seed drying. Observing real-world success stories helped participants internalize the theoretical knowledge acquired in earlier training. 4) Implementation on individual learning plots: Following the capacity-building activities, members were encouraged to apply their new knowledge through practice. Each participant established a personal learning plot on their own land, using the recommended practices to cultivate Khon Kaen 6 peanuts. This hands-on experience served as both a trial and demonstration for improved techniques, including the use of gypsum and lime to adjust soil pH and calcium levels, and proper drying methods to reduce seed moisture to the ideal level of 7-8%, thus maintaining seed viability and minimizing fungal contamination. 5) Monitoring, evaluation, and knowledge sharing: Regular peer visits and group reflections were conducted to monitor progress, exchange experiences, and address emerging challenges. This ongoing cycle of feedback allowed members to learn from one another and refine their practices. Particular attention was paid to maintaining varietal purity through consistent monitoring, field inspection, and rogueing of off-type plants during key growth stages such as flowering, pod development, and harvest. Laboratory tests were also conducted to assess moisture content, germination rate, seed vigor, and purity, following ISTA guidelines. Accelerated aging tests were performed to evaluate seed vigor under stressful storage conditions. The collaborative efforts resulted in a significant improvement in both the quantity and quality of peanut seed production. The average yield of Khon Kaen 6 peanuts increased to 557 kilograms of dry pods per rai, a marked improvement compared to previous years. Moreover, the purity of the harvested seeds improved, with a noticeable reduction in contamination by off-types and malformed or shriveled pods. Farmers reported a decline in the number of pods producing a hollow sound when pressed, indicating better seed development. The initiative also promoted post-harvest improvements. Members adopted standardized drying practices, using mesh trays and regularly turning the pods to ensure even drying and reduce the risk of fungal infection. Seed cleaning and grading were performed using mechanical equipment to remove impurities and damaged pods, ensuring seed lots met quality certification standards. Beyond immediate production gains, this initiative fostered a spirit of innovation and experimentation among Center members. Encouraged by the success of improved Khon Kaen 6 seed production, several farmers began experimenting with other peanut varieties to diversify their seed-saving activities. Furthermore, enhanced soil fertility through organic matter incorporation and the use of crop residues as green manure has led to improved growth of subsequent crops in rotation systems. The project also highlighted the importance of combining indigenous knowledge with scientific guidance. The integration of local experience and expert advice created a robust knowledge system that was both accessible and practical for small-scale farmers. As a result, the Community Legume Seed Production Center is now better positioned to serve as a local hub for sustainable seed production, knowledge dissemination, and community-based agricultural development. In summary, this case demonstrates that participatory, experiential, and knowledge-based approaches can significantly enhance seed production among smallholder farmers. By leveraging group collaboration, technical training, and practical field application, the Community Legume Seed Production Center has achieved tangible improvements in seed quality, yield, and sustainability. This model holds promise for replication in other regions where smallholder farmers seek to enhance seed security and agricultural resilience through community-driven innovation.